An analysis on the role of word formation process in the lyrics of Malaysia’s top 10 English songs - Ong, Su Ke (2022)

(untitled)
The beauty of language is that it encourages evolution and changes to its contents. Being a sign of vitality (Yule, 2016), the changes of language use is shaped by its users to accommodate the changing paces of mankind. This study aims to understand the role of recent language changes by analysing the literary work of its users – song lyrics. Under the morphological concept of the word formation process, new instances of language uses are categorized into word formation process types such as Acronyms, Derivation, Backformation, Conversion, Compounding, Borrowing, Coinage, Clipping, and Blending. These categories are then compared to understand the trends of how language is changing. Setting the scope to the trends of language use in Malaysia, this study analyses the 10 most popular English songs amongst Malaysians to gain a more local insight on what types of word formation processes might influence their use of language. Findings of this study suggests that language change is vigorously evident in writings, with the most prominent word formation process being conversions. This study hopes to normalise and encourage the change and vitality, and creative use of language, especially in Malaysian context.